Apoptotic suppression by baculovirus P35 involves cleavage by and inhibition of a virus-induced CED-3/ICE-like protease. - Bertin, J (1996)
Baculovirus p35 prevents programmed cell death in diverse organisms and encodes a protein inhibitor (P35) of the CED-3/interleukin-1 beta-converting enzyme (ICE)-related proteases. By using site-directed mutagenesis, we have identified P35 domains necessary for suppression of virus-induced apoptosis in insect cells, the context in which P35 evolved. During infection, P35 was cleaved within an essential domain at or near the site DQMD-87G required for cleavage by CED-3/ICE family proteases. Cleavage site substitution of alanine for aspartic acid at position 87 (D87A) of the P1 residue abolished P35 cleavage and antiapoptotic activity. Although the P4 residue substitution D84A also caused loss of apoptotic suppression, it did not eliminate cleavage and suggested that P35 cleavage is not sufficient for antiapoptotic activity. Apoptotic insect cells contained a CED-3/ICE-like activity that cleaved in vitro-translated P35 and was inhibited by recombinant wild-type P35 but not P1- or P4-mutated P35. Thus, baculovirus infection directly or indirectly activates a novel CED-3/ICE-like protease that is inhibited by P35, thereby preventing virus-induced apoptosis. Our findings confirmed the inhibitory activity of P35 towards the CED-3/ICE protease, including recombinant mammalian enzymes, and were consistent with a mechanism involving P35 stoichiometric interaction and cleavage. P35's inhibition of phylogenetically diverse proteases accounts for its general effectiveness as an apoptotic suppressor.